Linking Sport Simulation Games to Real-World Sport Consumption: The Role of Passion and Sport Enjoyment - Jeeyoon Kim (Journal of Applied Sports Management, 2026)
This study examines the potential of utilizing sport simulation games in promoting real-world sport consumption. Drawing on diversification theory, we examine whether psychological experiences (arousal, belonging, achievement) in simulated sport play leads to sport enjoyment and subsequently increases sport consumption intentions (participating, spectating, media viewing); passion-type (harmonious vs. obsessive) is set as a boundary condition based on the dualistic model of passion. Using online survey data from 431 US/Canadian adults who regularly play sport simulation games, multi-group SEM was conducted. In harmonious group, arousal and belonging were positively linked to all three intention-types through sport enjoyment, supporting a positive relation (i.e., synergy) between gaming and sport. In obsessive group, arousal and achievement were positively linked to sport media viewing intention through sport enjoyment, but a stronger negative link between achievement and sport participation intention was also observed, indicating an overall negative relation (i.e., competing). Theoretical and practical implications are discussed.
Keywords: Sport simulation game; arousal; belonging; achievement; sport enjoyment; harmonious passion; and obsessive passion